1997
DOI: 10.1099/00221287-143-10-3165
|View full text |Cite
|
Sign up to set email alerts
|

Fungicides and sterol-deficient mutants of Ustilago maydis: plasma membrane physico-chemical characteristics do not explain growth inhibition

Abstract: Plasma membrane vesicles from erg1 I and erg2 sterol-deficient mutants and from wild-type Ustilago maydis sporidia treated with and without inhibitors of sterol 14a-demethylase or sterol A8-A7 isomerase (triadimenol and fenpropimorph fungicides, respectively) were purified by aqueous two-phase partitioning. Changes in plasma membrane lipid composition were mostly restricted to sterols and complex lipid-bound fatty acids (CLB fatty acids). There was a greater accumulation of abnormal sterols (14a-methyl-or A8-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…It could be argued that this activation may be due to other causes such as increased polypeptide amounts in membrane or changes in fluidity. We have shown previously that these two factors remain largely unchanged in the same conditions used in this study [18,21].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…It could be argued that this activation may be due to other causes such as increased polypeptide amounts in membrane or changes in fluidity. We have shown previously that these two factors remain largely unchanged in the same conditions used in this study [18,21].…”
Section: Discussionsupporting
confidence: 63%
“…A␣close correlation ( r =0.98) was observed, and this was independent of the kind of genetic lesion or inhibitor used, suggesting that this activating effect was indeed caused by the fatty acid/lipid environment of the ATPase. It must be noted that triadimenol and fempropimorph have no effect on ATPase activity in these conditions [21]. The 18 : 2/18 : 1 ratio in untreated wild‐type was close to unity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, no report has dealt with the effects that abnormal-sterol accumulation may have on the fungal plasma membrane H ϩ -ATPase, although the lipid composition of the plasma membrane is thought to be of great importance in membrane-bound enzyme activity. In another publication, we showed that it is useful to make a comparison between the effects of a fungicide on abnormal-sterol composition and those found in a mutant with a genetic block in the sterol biosynthesis pathway at the point where the fungicide is presumed to act (6). These comparisons showed that the fungicides produced effects, similar to stress adaptation processes, which were not found in the mutants (6).…”
mentioning
confidence: 90%